Biogeochemical Distinctiveness of Peatland Ponds, Thermokarst Waterbodies, and Lakes - Arsenault, Julien; Talbot, Julie; Brown, Lee E.; Holden, Joseph; Martinez-Cruz, Karla; Sepulveda-Jauregui, Armando; Swindles, Graeme T.; Wauthy, Maxime; Lapierre, Jean-Francois (My University, 2022)
Small lentic freshwater ecosystems play a disproportionate role in global biogeochemical cycles by processing large amounts of carbon (C), nitrogen (N), and phosphorus (P), but it is unlikely that they behave as one homogenous group for the purpose of extrapolation. Here, we synthesize biogeochemical data from >12,000 geographically distinct freshwater systems: lakes, peatland ponds, and thermokarst waterbodies. We show that peatland ponds are biogeochemically distinct from the more widely studied lake systems, while thermokarst waterbodies share characteristics with peatland ponds, lakes, or both. For any given size or depth, peatland ponds tend to have dissolved organic carbon concentrations several-fold higher and are 100-fold more acidic than lakes because of the organic matter-rich settings in which they develop. The biogeochemical distinctiveness of freshwater ecosystems highlights the need to account for the fundamental differences in sources and processing of organic matter to understand and predict their role in global biogeochemical cycles.
Keywords: peatland ponds; lakes; thermokarst waterbodies; biogeochemistry; carbon; nutrients